2014
DOI: 10.1002/cssc.201300970
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐Life Treatment of Poly(Vinyl Chloride) and Chlorinated Polyethylene by Dehydrochlorination in Ionic Liquids

Abstract: There is an urgent need for green technologies to remove halogens from halogenated polymers at the end of their lifetime. Ionic liquids (ILs) were used to dehydrochlorinate and/or dissolve the chlorinated polymers poly(vinyl chloride) (PVC) and chlorinated polyethylene (CPE). The dehydrochlorination activity of an IL depends mainly on its anion and is related to the high hydrogen-bond-accepting ability (β value) of the anion. Different phosphonium ILs successfully dissolve and dehydrochlorinate PVC and CPE at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…Glas et. al also found that for a stearate stabilized PVC (like the one used in this study) the stabilizer has only a minor effect under these harsh conditions, since the rate of de-hydrochlorination is now only slightly affected by the presence of heat stabilizer 20 . In a previous paper, we have shown that the thermal stability of PVC plasticized with dioctyl phthalate (DOP), whose effectiveness is well known owing to the good solvent ability toward PVC, is very similar to that of neat PVC 21 .…”
Section: Accepted Manuscriptsupporting
confidence: 56%
See 1 more Smart Citation
“…Glas et. al also found that for a stearate stabilized PVC (like the one used in this study) the stabilizer has only a minor effect under these harsh conditions, since the rate of de-hydrochlorination is now only slightly affected by the presence of heat stabilizer 20 . In a previous paper, we have shown that the thermal stability of PVC plasticized with dioctyl phthalate (DOP), whose effectiveness is well known owing to the good solvent ability toward PVC, is very similar to that of neat PVC 21 .…”
Section: Accepted Manuscriptsupporting
confidence: 56%
“…In a recent paper 20 , Glas et al used several ILs (different to those used in this study) to study the de-hydrochlorination of PVC for recycling purposes. Although the IL concentration these authors used was much higher than that used in our work (PVC was generally 5wt% of the PVC-IL mixture), they found that the onset temperature for de-hydrochorination of un-stabilized PVC was lower for a phosphonium rather than a nitrogen containing IL because of the higher swelling ability of the former.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[159] Polyvinyl chloride (PVC)-based wastes emanate significantly hazardous byproducts of HCl, Cl 2 , and organochlorine compounds. [160][161][162] Interestingly, product derived from recycled plastic results in energy savings of 50-60% compared to that made from fresh resin. [163] Besides conventional conversion techniques, transfiguration of polymers into carbonaceous materials via controlled carbonization has proven to be an effective way of valorizing waste polymer into high-value carbon.…”
Section: Waste Polymer-derived Carbon As Supercapacitor Electrodesmentioning
confidence: 99%
“…251,252 Glas et al described a process for the end-oflife treatment of PVC that demonstrated how the use of [P 4444 ]Cl allowed the dehydrochlorination and/or dissolution of the chlorinated polymers poly(vinylchloride) (PVC) and chlorinated polyethylene (CPE). 253 Swelling and shrinking photoresponsive phosphonium-based ionogel microstructures were investigated by Lopez and co-workers. It was found that the [P 66614 ][NTf 2 ] ionogel allowed the highest degree of swelling.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%